Dietary Burden of Phenolics per Serving of “Mountain Tea” (Sideritis) from Macedonia and Correlation to Antioxidant Activity - Petreska, Jasmina; Stefova, Marina; Ferreres, Federico; Moreno, Diego. A.; Tomás-Barberán, Francisco. A.; Stefkov, Gjose; Kulevanova, Svetlana; Gil-Izquierdo, Angel (SAGE Publications, 2011)
This work was afforded from 2 points of view, phytochemical evaluation and relation to antioxidant activity and dietary burden of phenolics of a cup of “Mountain tea”, a drink obtained by domestic infusion of Sideritis. Phytochemically, two extraction protocols using water and methanol as solvent were used for comparison. Methanol and boiling water extracts (by domestic infusion procedure) showed that extracts were rich in bound forms of phenolics such as hydroxycinnamic acids, phenylethanoid glycosides and flavonoid glycosides. The total phenolic content for Sideritis species ranged around 190 mg per serving (2 g infusion bag) for methanol extracts and around 72 mg per serving in water extracts. Among the two different Macedonian Sideritis species, Sideritis raeseri (wild growing) showed the highest phenolics content in both extracts (212 mg and 89 mg per serving, respectively). Concerning the phenolic content in the different aerial parts, leaf was the richest plant organ in phenolics followed by flower and stem with the lowest amount. The methanol extract from Sideritis raeseri (wild growing) showed the highest antioxidant capacity as shown by DPPH, ABTS and FRAP assays. The antioxidant capacity was linearly correlated with phenolic content. Nutritionally, the dietary burden of phenolics of a “Mountain tea” bag for domestic infusion (serving size) was established at 89 mg for an homogeneous and equal distribution of the different aerial parts (leaf, flower and stem). However, and according to our results a rate of 60% leaf and 40% flower would increase the content of bioavailable phenolics and also the total phenolics content of a serving bag of “Mountain tea”.